Influence of family background on academic achievements among nursing students at Universiti Sains Malaysia health campus - Adam, Nursyazana (Universiti Sains Malaysia, 2023)
This study was aimed to investigate the family background factors that can influence students’ academic achievement among nursing students at Universiti Sains Malaysia Health Campus. This was quantitative study and cross-sectional study design was used in this research to gather the information from nursing students in Universiti Sains Malaysia Health Campus. The questionnaire used in this study was family background influence questionnaire (FBIQ) from Ugwuja. G (2010). A total of 80 respondents participated in this study. Data collected were statistically analysed using the SPSS software version 26.0. Pearson’s Chi-square was used for data analysis. There is no association between socio-demographic data (parents’ income) and students’ academic achievement (p>0.05). While, there is an association between socio-demographic data (parents’ level of education) and students’ academic achievement (p<0.05). However, based on the result of this study, respondents agreed that parent’s level of education can influenced students’ academic achievement as the educated parents always want their children to be educated (questionnaire item number 1 until 7) with mean score above 2.50. The respondents also agreed that parental motivation also influenced students’ academic achievement with mean score 3.44. Based on these results, the study suggested among other things that parents should expand their sources of income in order to be able to pay for the education of their children. Parents should understand how important it is to motivate children using rewards and other methods